2020
DOI: 10.3389/fphy.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Manifestation of Evanescent Wave in Biomedical Application

Abstract: The idea of the proposed paper is a demonstration of the evanescent wave effect on nano-objects of inorganic and organic (in particular, formed blood elements) origin localized in a biological medium, in the direction perpendicular to the direction of the Pointing vector action. On the one hand, this opens up (illustrates) new possibilities in the optical control of the direction of motion and speed of the studied nanoobjects in a layer of biological fluid. On the other hand, the very choice of objects of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Applied aspects of the research reported in this paper are associated with additional possibilities for optical manipulation, especially in biological and medical applications because many bio-tissues are characterized by the remarkable optical anisotropy [23]. Besides, the highly adaptive and flexible optical traps can be used for controllable delivering and distribution of biologically active species at the cellular and sub-cellular scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applied aspects of the research reported in this paper are associated with additional possibilities for optical manipulation, especially in biological and medical applications because many bio-tissues are characterized by the remarkable optical anisotropy [23]. Besides, the highly adaptive and flexible optical traps can be used for controllable delivering and distribution of biologically active species at the cellular and sub-cellular scales.…”
Section: Discussionmentioning
confidence: 99%
“…In case when the evanescent wave is formed in the process of total internal reflection from the prism surface, the SM direction is determined by input beam polarization. The experimental observation of this "extraordinary" SM [8] in evanescent waves requires a more exquisite technique [21] than that was used in the case of paraxial beams [18,19], but it has also been demonstrated with the help of anisotropic birefringent objects [22,23]. The unique peculiarity of these demonstrations was the micro-object's motion in a direction different from the Poynting-vector direction.…”
Section: Introductionmentioning
confidence: 99%
“…The useful features of the presented approach are directly associated with the employment of the high-precision optical tweezer, which is one of the numerous examples of structured light fields that constitute a set of new, extremely suitable instruments for nano-scale diagnostics and technologies [21,[35][36][37]. In the optical tweezer discussed above, the light's spatial structure plays a decisive role; however, the complex polarization and spectral structures of probing light fields offer additional promising possibilities in the roughness diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…The main idea of this work was to show the possible connections among optics, electromagnetic and sound waves and where the acoustic spin density can bring interest by studying the remarked similarities among evanescent waves [25,26,27,28]. Using this kind of analogies may be helpful to explore new possibilities in the acoustic control of the direction of motion and speed of nano-objects in a layer of biological fluid as the red blood cells [39,40].…”
Section: Discussionmentioning
confidence: 99%